Political judgment and the constitution of the common in Arendt - Correia, Adriano (HannahArendt.net, 2025)
In this text, I examine the relationship between political judgment and the constitution of a common world in the thought of Hannah Arendt. In this analysis, I argue that totalitarianism emerged from processes of social atomization and isolation. These processes destroyed shared reality by eliminating plural perspectives and common sense. For Arendt, reality is dependent on a common world sustained by the presence of others who perceive and interpret it differently. The present study aims to elucidate Arendt’s concept of understanding as an ongoing, imaginative process through which individuals achieve a state of reconciliation with reality, independently of fixed categories. This capacity is closely linked to judgment, especially as developed through Arendt’s reading of Immanuel Kant. Reflective judgment, grounded in imagination, enables individuals to consider multiple perspectives and form opinions within a shared public space. Totalitarian regimes destroy both the common world and the capacity for judgment by fostering loneliness, ideological uniformity, and the collapse of distinctions between truth and falsehood. In contrast, political judgment depends on plurality and communicability. It requires adopting an "enlarged mentality" that considers the viewpoints of others. I ultimately argue that the common world is both the condition of and the product of political judgment. This world is constituted through interaction, speech, and the exchange of perspectives. I conclude that sustaining this shared world is essential in contemporary contexts marked by fragmentation because the loss of plurality erodes reality and political life itself.